A Case of Septum Pellucidum Agenesis in a Patient with Psychotic Symptoms - Alexander Kilpatrick; Heela Azizi; Joshua Jay; Cecilia Canale; Jeffrey Balkenbush; Filipa Cardoso; Hashem Kalbouneh; Tasmia Khan; Isaac Kim; Alexa Kahn; Paul Saad; Deepa Nuthalapati; et al. (Case Reports in Psychiatry)
Agenesis of the septum pellucidum is a rare congenital defect that has been associated with psychiatric disorders, cognitive deficits, learning disabilities, seizures, and neuropsychiatric disturbances. We present the case of a patient with partial agenesis of the septum pellucidum who exhibits disorganized behavior and paranoid and persecutory delusions. We add to the literature of incidental neuropsychiatric symptoms in patients with partial agenesis of the septum pellucidum which is an area that requires further exploration and study. We discuss the implications of these findings in light of previous literature findings.